1975
DOI: 10.1021/ic50148a031
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of tetraphenylarsonium tris(benzenedithiolato)tantalate(V)

Abstract: The crystal and molecular structure of tetraphenylarsonium tris(benzenedithiolato)tantalate(V), [(CsHs^As] [Ta(S2C6Ü4)3], has been determined from three-dimensional X-ray diffraction methods using data collected with an automated diffractometer.The compound crystallizes in the triclinic space group P\ (No. 1) with one molecule per unit cell of dimensions a = 9.442 (1), b = 9.752 (1), c = 11.872 (2) A and a = 77.37 (1), ß = 71.20 (1), y = 74.23 (1)°. The observed and calculated densities are 1.67 (2) and 1.66 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
4

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 3 publications
1
14
1
4
Order By: Relevance
“…In neuerer Zeit wurden die ersten nichtoktaedrischen sechsfach koordinierten Komplexe mit einzähnigen Thiolatliganden beschrieben. ¾hnliche Verzerrungen wurden bereits früher beobachtet, [95] und bei heteroleptischen Komplexen erlangen sie gröûere Bedeutung (Abschnitt 4.3). In Abhängigkeit von der jeweiligen Elektronenkonfiguration, vom Ligandentyp, vom Metallzentrum sowie von Wechselwirkungen mit Gegenionen decken diese Strukturen den gesamten Bereich von oktaedrischer bis trigonal-prismatischer Koordination ab.…”
Section: Nichtoktaedrische Sechsfach Koordinierte Komplexeunclassified
“…In neuerer Zeit wurden die ersten nichtoktaedrischen sechsfach koordinierten Komplexe mit einzähnigen Thiolatliganden beschrieben. ¾hnliche Verzerrungen wurden bereits früher beobachtet, [95] und bei heteroleptischen Komplexen erlangen sie gröûere Bedeutung (Abschnitt 4.3). In Abhängigkeit von der jeweiligen Elektronenkonfiguration, vom Ligandentyp, vom Metallzentrum sowie von Wechselwirkungen mit Gegenionen decken diese Strukturen den gesamten Bereich von oktaedrischer bis trigonal-prismatischer Koordination ab.…”
Section: Nichtoktaedrische Sechsfach Koordinierte Komplexeunclassified
“…Indeed, crystallographic investigations showed that tris(dithiolene) complexes such as [Mo(mnt) 3 ] 2-(mnt = maleonitriledithiolate(2-)) and [Mo(bdt) 3 ] 1-(bdt = benzene-1,2-dithiolate(2-)) adopt a geometry between trigonal prismatic and octahedral; 6,7 however, there are some notable exceptions such as [Mo(mdt) 3 ] z (mdt = 1,2-dimethylethene-1,2-dithiolate(2-), z = 2-, 1-), where the Mo-S 6 trigonal prism is maintained throughout the series, and [Ta(bdt) 3 ] 1-, which is isoelectronic with [Mo(S 2 C 2 H 2 ) 3 ] but forms a distorted octahedron. [8][9][10] Another factor thought to stabilize the trigonal prism was interligand sulfur-sulfur bonding. However, this was refuted by comparing the S-S distances in the trigonal prismatic complexes [Mo(bdt) 3 Rotation about the C 3 axis from O h (θ = 60°) to D 3h (θ= 0°), which is the pathway used to explain the racemization of certain octahedral tris(chelate) complexes, is known as a Bailar twist (Scheme 1b, θ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the decreasing stability of TP geometry in the order Mo > Nb > Zr suggested to Cowie and Bennett (1 1) that the proper matching of metal d-orbital and ligand orbital energies was an important condition for TP geometry, the study was not conclusive because the change in overall charge of the complexes should also favor the observed trend. To confirm the hypothesis of Cowie and Bennett, we undertook structural analysis of Ta(bdt)3-and Sb(bdt)3-complexes, which strongly resemble the Nb complex in metal size and also have the same charge (12,16). The increasing distortion away from TP geometry in the order Nb < Ta < Sb provides substantial evidence that the stability of TP Can.…”
Section: Introductionmentioning
confidence: 92%
“…All other features were less than 0.37e/A3. The programs used in this study are those described previously (12). Atomic coordinates and equivalent isotropic thermal parameters for the complex anion ~b ( e d t )~~-are listed in Table 4.…”
Section: X-ray Analysis Ofmentioning
confidence: 99%
See 1 more Smart Citation